Restoring Visual Acuity in Dynamic Conditions with a Vestibular Implant - Guinand, Nils; Van de Berg, Raymond; Cavuscens, Samuel; Stokroos, Robert; Ranieri, Maurizio; Pelizzone, Marco; Kingma, Herman; Guyot, Jean-Philippe; Pérez Fornos, Angélica (Frontiers in Neuroscience, 2016)
Vestibular implants are devices designed to rehabilitate patients with a bilateral vestibular loss (BVL). These patients lack a properly functioning vestibulo-ocular reflex (VOR), which impairs gaze stabilization abilities and results in an abnormal loss of visual acuity (VA) in dynamic situations (i.e., severely limiting the patient’s ability to read signs or recognize faces while walking). We previously demonstrated that the VOR can be artificially restored in a group of BVL patients fitted with a prototype vestibular implant. This study was designed to investigate whether these promising results could be translated to a close-to-reality task, significantly improving VA abilities while walking. Six BVL patients previously implanted with a vestibular implant prototype participated in the experiments. VA was determined using Sloan letters displayed on a computer screen, in four conditions: (1) with the patient standing still without moving (static), (2) while the patient was walking on a treadmill at constant speed with the vestibular implant prototype turned off (systemOFF), (3) while the patient was walking on a treadmill at constant speed with the vestibular implant prototype turned on providing coherent motion information (systemONmotion), and (4) a “placebo” condition where the patient was walking on a treadmill at constant speed with the vestibular implant prototype turned on providing reversed motion information (systemONsham). The analysis (one-way repeated measures analysis of variance) revealed a statistically significant effect of the test condition (F(3,12) = 30.5, p<0.001). Significant decreases in VA were observed with the systemOFF condition when compared to the static condition (Tukey post-hoc p<0.001). When the vestibular implant was turned on,delivering pertinent motion information (systemONmotion) the VA improved to close to normal values. The improvement disappeared in the placebo condition (systemONsham) and VA values also dropped significantly in this condition (Tukey post-hoc p<0.001). These results are a significant step forward in the field, demonstrating for the first time in humans that gaze stabilization abilities can be restored with a vestibular implant prototype. The vestibular implant shows considerable promise of being the first-ever effective therapeutic alternative for patients with a BVL in the near future.